(untitled) (Journal of Engineering, 2019)
In this study, the investigation of Local natural Iraqi rocks kaolin with the addition of different proportions of bauxite and its effect on the physical and mechanical properties of the produced refractories was conducted. Kaolin/bauxite mixture was milled and classified into various size fractions, the kaolin (less than 105 μm) and the bauxite (less than 70μm). The specimens were mixed from kaolin and bauxite in ranges B1 (95+5)%, B2 (90+10)%, B3(85+15)%, and B4 (80+20)% respectively. The green specimens were shaped by the semi-dry method using a hydraulic press and a molding pressure of 7 MPa with the addition of (9-12) %wt. of PVA ratio. After molding and drying, the specimens were fired at (1100, 1200 and 1300) °C. Physical properties (density, porosity, water absorption) and mechanical properties (indirect tensile strength and hardness) were measured for all the prepared samples. The results showed that the porosity was increased and the density was decreased, such increase and decrease affected on to the mechanical properties for refractory. The highest values of indirect tensile strength and hardness were obtained at 20% Bauxite at 1300 °C (0.85386 MPa, 1411Kg / mm²) respectively.